Low Bone Mineral Density and Risk of Incident Fracture in HIV-Infected Adults. Issue 1 (January 2016) - Battalora, Linda; Buchacz, Kate; Armon, Carl; Overton, Edgar T; Hammer, John; Patel, Pragna; Chmiel, Joan S; Wood, Kathy; Bush, Timothy J; Spear, John R; Brooks, John T; Young, Benjamin; et al.
Background: Prevalence rates of low bone mineral density (BMD) and bone fractures are higher among HIV-infected adults compared with the general United States (US) population, but the relationship between BMD and incident fractures in HIV-infected persons has not been well described. Methods: Dual energy X-ray absorptiometry (DXA) results of the femoral neck of the hip and clinical data were obtained prospectively during 2004-2012 from participants in two HIV cohort studies. Low BMD was defined by a T-score in the interval >-2.5 to <-1.0 (osteopenia) or ≤-2.5 (osteoporosis). We analysed the association of low BMD with risk of subsequent incident fractures, adjusted for sociodemographics, other risk factors and covariables, using multivariable proportional hazards regression. Results: Among 1, 006 participants analysed (median age 43 years [IQR 36–49], 83% male, 67% non-Hispanic white, median CD4 + T-cell count 461 cells/mm 3 [IQR 311–658]), 36% ( n =358) had osteopenia and 4% ( n =37) osteoporosis; 67 had a prior fracture documented. During 4, 068 person-years of observation after DXA scanning, 85 incident fractures occurred, predominantly rib/sternum ( n =18), hand ( n =14), foot ( n =13) and wrist ( n =11). In multivariable analyses, osteoporosis (adjusted hazard ratio [aHR] 4.02, 95% CI 2.02, 8.01) and current/prior tobacco use (aHR 1.59, 95% CI 1.02, 2.50) were associated with incident fracture. Conclusions: In this large sample of HIV-infected adults in the US, low baseline BMD was significantly associated with elevated risk of incident fracture. There is potential value of DXA screening in this population.